Kajian Kualitas Air Sungai - Nurma Ani; Arman Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the water quality of the Aek Pala River in Labuhanbatu Regency. The method used is a survey method with qualitative and quantitative analysis. The results showed that the water of the Aek Pala River was slightly cloudy, odorless and had a TDS level of 164.60 mg/l, pH = 6.85; BOD = 9.08; COD = 20.78; phosphate < 0.003 mg/l; nitrate = 3.04 mg/l; total Coliform = 9.17 CFU/100 ml; and E. coli = 0.03 CFU/100 ml. In conclusion, the physical, chemical and microbiological parameters of the Aek Pala River water are still in the safe category in meeting drinking water quality standards and are worthy of being used as a bathing tourist attraction for people around Labuhanbatu and other areas. Keywords: BOD, COD, E. coli, Water Quality, Nitrate, pH, Phosphate, Aek Pala River, TDS, Total Coliform